007 Multi-modal imaging of anomalous left coronary artery off the pulmonary artery (ALCAPA). (5th May 2016) - Jayawardhana, Kavin; Abbas, Ausami; Harden, Stephen; Peebles, Charles; Shambrook, James
Abstract : Introduction: Although first described in 1866, ALCAPA was recognised with a clinical description and correlation with autopsy findings by Bland and colleagues in 1933. ALCAPA accounts for approximately 0.25–0.5% of all congenital heart defects and exists predominantly in two forms; infant type and adult type. Infants present with features of myocardial ischaemia and heart failure and very rarely can be associated with other cardiac anomalies. Mortality rate approaches 90% in infants if ALCAPA is left untreated. Adult cases are unusual and but can present with unusual ischaemic symptoms. Although historically ALCAPA was diagnosed at conventional angiography, the development of gated CT and MRI imaging allows assessment with non-invasive means. Learning Objectives: To describe and illustrate radiological findings and characteristics in patients diagnosed with having an ALCAPA anomaly. Imaging Findings: We describe our case series of patients with characteristic findings on electrocardiography, CT and MRI seen in patients with ALCAPA. The left coronary artery arises from the pulmonary trunk and branches into dilated LAD and circumflex vessels. Collaterals are usually seen between the right and left coronary arteries with retrograde flow through the left coronary artery into the pulmonary trunk. The right coronary artery is often also dilated due to high volume flow. Identification of these dilated collaterals is often the first indication of this pathology. Conclusion: It is important for radiologists to be aware of the typical imaging findings in this relatively rare anomaly as prognosis is good with early diagnosis and surgical correction.